2001
DOI: 10.1016/s0370-1573(00)00112-5
|View full text |Cite
|
Sign up to set email alerts
|

CP violation in top physics

Abstract: CP violation in top physics is reviewed. The Standard Model has negligible effects, consequently CP violation searches involving the top quark may constitute the best way to look for physics beyond the Standard Model. Non-standard sources of CP violation due to an extended Higgs sector with and without natural flavor conservation and supersymmetric theories are discussed. Experimental feasibility of detecting CP violation effects in top quark production and decays in high energy e + e − , γγ, µ + µ − , pp and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
154
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 291 publications
(705 reference statements)
0
154
0
Order By: Relevance
“…[10] and references therein. As to top quark spin phenomena at hadron colliders there exists an extensive literature on theoretical investigations within the standard model (SM) [11,12,13,14,15,16,17,18,19] and beyond [20,21,22,23,24,25,26,27,28,29,30,31,32]. Yet the precision of these analyses -in particular within the SM -must be increased for the data samples that will be recorded at the Tevatron and at the LHC to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…[10] and references therein. As to top quark spin phenomena at hadron colliders there exists an extensive literature on theoretical investigations within the standard model (SM) [11,12,13,14,15,16,17,18,19] and beyond [20,21,22,23,24,25,26,27,28,29,30,31,32]. Yet the precision of these analyses -in particular within the SM -must be increased for the data samples that will be recorded at the Tevatron and at the LHC to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…For convenience, we define two reduced couplings: c t = y t cos θ/y t SM andc t = y t sin θ/y t SM in the following calculations. Although the CP-violating interaction can contribute to the electric dipole moment (EDM), the bounds on the couplingc t rely on the assumption of Higgs couplings to other light fermions [104,105]. Given that these couplings are generally unobservable at the LHC, we do not impose EDM constraints in this study.…”
Section: Jhep01(2015)008mentioning
confidence: 99%
“…The chargino masses are eigenvalues of the diagonalized mass matrix, X, given by 5) where M 2 is the soft SUSY-breaking SU(2) L gaugino mass parameter and µ is the Higgsino mass parameter. The relevant Lagrangian terms for the quark-down squark-chargino interaction are given by 6) where the index σ refers to chargino mass eigenstates. Y diag u,d are the diagonal up-and downquark Yukawa couplings, and V , U the chargino rotation matrices defined by , 2, 3, 4) are four-component Majorana fermions.…”
Section: The Cp Structure In the Chargino And Neutralino Sectors mentioning
confidence: 99%
“…We showed that, although the channelsts andcs have sizable CP asymmetry with respect to the channelstb andcb, this result has to be taken with caution since the formers have very small branching ratios (Br's) which makes them harder to observe. We calculated (A 2 CP × Br) −1 [4] for each decay mode, which is proportional to the number of required charged Higgs bosons produced at colliders 1 to observe an asymmetry for a given channel [4,5,6]. Based on this analysis, we concluded that H − →cb and H − →tb are the the optimal channels which could reveal a measurable CP asymmetry at the order of 10 − 15%.…”
Section: Introductionmentioning
confidence: 99%